2016
DOI: 10.1111/phn.12264
|View full text |Cite
|
Sign up to set email alerts
|

Using Omaha System Documentation to Understand Physical Activity among Rural Women

Abstract: PHNs should assess rural women who are not physically active for potentially serious physiological, psychosocial, and environmental problems. Departmental policies requiring assessment of Omaha System data across programs enabled population health measurement and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Future studies should examine correlations between health‐related behavior problems and the feasibility of implementing interventions that simultaneously target multiple behaviors. Finally, education is a common component of physical activity interventions, and prior studies have reported a positive association between physical activity knowledge and behavior (Fredriksson et al, ; Hui, Hui, & Xie, ; Olsen, Thorson, et al, ). Yet, in this study, Physical activity knowledge was essentially the same among those who were completely inactive and those who were marginally active.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future studies should examine correlations between health‐related behavior problems and the feasibility of implementing interventions that simultaneously target multiple behaviors. Finally, education is a common component of physical activity interventions, and prior studies have reported a positive association between physical activity knowledge and behavior (Fredriksson et al, ; Hui, Hui, & Xie, ; Olsen, Thorson, et al, ). Yet, in this study, Physical activity knowledge was essentially the same among those who were completely inactive and those who were marginally active.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological model for health promotion (McLeroy et al, ) was used to guide this study. The model recognizes the influence of the social–ecological environment on health behaviors and was operationalized with the Omaha System using a process described in prior studies (Olsen, Horning, et al, ; Olsen et al, ; Olsen, Thorson, et al, ). In summary, the intrapersonal, interpersonal, and community levels of the model were aligned with the Physiological, Psychosocial, and Environmental domains and problems of the Omaha System Problem Classification Scheme, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the forefront of evidence-based family home visiting practice, public health nurses (PHNs) in local and state public health agencies routinely provide home visits to high risk families [9,10,[13][14][15][16][17][18][19]. While many evidencebased home visiting programs target low-income, high risk first-time single parents, the PHN workforce especially in governmental agencies must respond to identified local needs.…”
Section: Introductionmentioning
confidence: 99%